BmK NT1-induced neurotoxicity is mediated by PKC/CaMKⅡ-dependent ERK1/2 and p38 activation in primary cultured cerebellar granule cells. (1st June 2019) - Shen, Liping; Yang, Qundi; He, Yuwei; Zou, Xiaohan; Cao, Zhengyu
Abstract: Voltage-gated sodium channels (VGSCs) represent molecular targets for a number of potent neurotoxins that affect the ion permeation or gating kinetics. BmK NT1, an α-scorpion toxin purified from Buthus martensii Karch (BMK), induces excitatory neurotoxicity by activation of VGSCs with subsequent overloading of intracellular Ca 2+ in cerebellar granule cells (CGCs). In the current study, we further investigated signaling pathways responsible for BmK NT1-induced neurotoxicity in CGCs. BmK NT1 exposure induced neuronal death in different development stages of CGCs with similar potencies ranging from 0.21−0.48 μM. The maximal neuronal death induced by BmK NT1 gradually increased from 25.6% at 7 days in vitro (DIVs) to 42.1%, 47.8%, and 67.2% at 10, 13, and 16 DIVs, respectively, suggesting that mature CGCs are more vulnerable to BmK NT1 exposure. Application of Ca 2+ /calmodulin-dependent protein kinase Ⅱ (CaMKⅡ) inhibitors, KN-62 or KN-93, but not Ca 2+ /calmodulin-dependent protein kinase kinase (CaMKK) inhibitor, STO-609, completely abolished BmK NT1-induced neuronal death. Moreover, BmK NT1 exposure stimulated CaMKⅡ phosphorylation. BmK NT1 also stimulated extracellular regulated protein kinases 1/2 (ERK1/2) and p38 phosphorylation which was abolished by tetrodotoxin demonstrating the role of VGSCs on BmK NT1-induced ERK1/2 and p38 phosphorylation. However, BmK NT1 didn't affect c-Jun N-terminal kinase (JNK) phosphorylation. In addition, both ERK1/2 inhibitor, U0126 and p38 inhibitor, SB203580 attenuated BmK NT1-induced neuronal death. Both PKC inhibitor, Gö 6983 and CaMKⅡ inhibitor, KN- 62 abolished BmK NT1-induced ERK1/2 and p38 phosphorylation. Considered together, these data demonstrate that BmK NT1-induced neurotoxicity is through PKC/CaMKⅡ mediated ERK1/2 and p38 activation.